Caroticocavernous Fistulae: Clinical Presentation, Imaging, and Endovascular Treatment - Khera, Pushpinder S.; Garg, Pawan K.; Tiwari, Sarbesh; Sureka, Binit; Yadav, Taruna; Purkayastha, Sukalyan; Bhaskar, Suryanarayanan; Bhatia, Pradeep; Morya, Arvind (Journal of Clinical Interventional Radiology ISVIR, 2019)
Caroticocavernous fistulas (CCFs) occur due to an abnormal communication between the high-pressure carotid artery system and the relatively lower pressure cavernous sinus system. They present with dramatic clinical presentations comprising among other things a swollen red eye with associated loss of vision to a varying degree. Blunt trauma sustained to the head, especially by two-wheeler riders, is the most common cause of the direct CCF and hence a practicing interventional radiologist in a developing country is very likely to encounter this entity in clinical practice. The authors intend to present a pictorial essay of the clinical presentations, imaging findings, endovascular management, and clinical follow-up for CCFs.
Keywords: caroticocavernous fistula; proptosis; embolization